Targeting GJB4 to inhibit tumor growth and induce ferroptosis in pancreatic cancer - Zheng, Xiangru; Li, Wenjun; Li, Xiaoli; Yao, Qianyi; Zheng, Luquan; Fan, Rongrong; Bie, Ping (Frontiers in Oncology, 2025)
BackgroundPancreatic cancer (PC) is a highly malignant type of cancer characterized by poor prognosis and high mortality rate. The role of gap junction protein beta 4 (GJB4) in PC has been scarcely reported. Therefore, the aim of this study was to investigate the function of GJB4 in PC cells and its potential as a therapeutic target.MethodsThe expression of GJB4 in patients with PC was examined using data from The Cancer Genome Atlas (TCGA), The Human Protein Atlas, Gene Expression Omnibus (GEO), Tumor Immune Estimation Resource (TIMER), microRNA Target Prediction Database (miRDB), and Encyclopedia of RNA Interactomes (ENCORI). A short hairpin-RNA lentiviral vector was employed to downregulate GJB4 in PC cells. The effects on tumor cell proliferation, invasion, and metastasis were assessed using cell proliferation assays, Transwell migration assays, wound healing assays, and subcutaneous xenograft models. Bioinformatics analysis was conducted to explore the function of GJB4 in PC cells. Changes in ferroptosis in PC cells following GJB4 downregulation were detected by immunofluorescence staining, transmission electron microscopy, and western blotting.ResultsGJB4 expression was found to be upregulated in PC tissues and positively correlated with patient survival. The expression of GJB4 was related to immune cell infiltration, tumor mutational burden expression and miRNAs. Downregulation of GJB4 inhibited the proliferation, metastasis, and invasion of PC cells, as well as tumor growth in nude mouse subcutaneous xenografts. Knockdown of GJB4 in PC cells disrupted oxidative and iron ion balance, and promoted ferroptosis, thereby inhibiting tumorigenic properties.ConclusionThe findings of this study indicate that downregulation of GJB4 may suppress tumor characteristics by promoting ferroptosis in PC cells. Therefore, GJB4 may be a promising therapeutic target for the treatment of PC.